NMR studies of anion-induced conformational changes in diindolylureas and diindolylthioureas - Makuc, Damjan; Hiscock, Jennifer R.; Light, Mark E.; Gale, Philip A.; Plavec, Janez (Beilstein Journal of Organic Chemistry, 2011)
The conformational properties of 1,3-diindolylureas and thioureas were studied by a combination of heteronuclear NMR spectroscopy and quantum mechanics calculations. NOE experiments showed that the anti–anti conformer along the C7–N7α bonds was predominant in DMSO-d6 solution in the absence of anions. Anion-induced changes in the 1H and 15N chemical shifts confirm the weak binding of chloride anions with negligible conformational changes. Strong deshielding of ureido protons and moderate deshielding of indole NH was observed upon the addition of acetate, benzoate, bicarbonate and dihydrogen phosphate, which indicated that the predominant hydrogen bond interactions occurred at the urea donor groups. Binding of oxo-anions caused conformational changes along the C7–N7α bonds and the syn–syn conformer was preferred for anion–receptor complexes. The conformational changes upon anion binding are in good agreement with energetic preferences established by ab initio calculations.
Keywords: anion recognition; conformation analysis; host–guest systems; NMR spectroscopy